DNA fingerprint and pathotype diversity of Pyricularia oryzae populations from Argentina - Consolo, Verónica Fabiana (2008)
The genetic diversity of the rice blast pathogen,Pyricularia oryzae, was analysed in rice-growing provinces of Argentina. A total of 161 isolates of the fungus was collected from 15 rice cultivars at nine locations during 2000-05 and characterised usingPot2-DNA fingerprinting. Based on DNA analysis (isolates with ≥70% band similarity), five lineages were identified and designated A, B, C,Dand E, with 11, 22, 4, 1 and 4 haplotypes identified, respectively. The predominant lineage, B, representing 38% of the collected isolates, was recovered from four cultivars in five locations. In contrast to lineages A and B, which did not contain a dominant haplotype, a single haplotype predominated in lineages C and E. Isolates representing all haplotypes were examined for virulence on a set of differential rice cultivars, near-isogenic lines and commercial cultivars commonly grown in Argentina, revealing 41 pathotypes and 24 international races. There was no significant association between DNA fingerprint similarities and pathotypes. Overall, these data indicated that populations ofP. oryzaein Argentina are genetically simple and predominantly clonal yet have a high pathotype diversity.